Pengaruh Promosi, Distribusi, Dan Harga Terhadap Minat Beli Ulang Produk Ready Meal (RTEM) Di Prima Freshmart Serang - Gugup Prihatma; Renaldy Decaprio (Universitas Serang Raya, 2024)
Research formulation: Does promotion have a significant effect on Repurchase Interest in Ready Meal (RTEM) products at PFM Serang. Does distribution have a significant effect on Repurchase Interest in Ready Meal (RTEM) products at PFM Serang? Does price have a significant effect on Repurchase Interest in Ready Meal (RTEM) products at PFM Serang? Do promotion, distribution and price have a significant effect on Repurchase Interest in Ready Meal (RTEM) products at PFM Serang. Promotion Research Results (X1) have no significant influence on Repurchase Interest (Y) in Ready Meal Products at PT Prima Freshmart in Serang City. Distribution (X2) has a significant influence on Repurchase Interest (Y) in Ready Meal Products at PT Prima Freshmart in Serang City. Price (X3) has a significant influence on Repurchase Interest (Y) in Ready Meal Products at PT Prima Freshmart in Serang City. There is a significant influence on Promotion (X1) Distribution (X2) and Price (X3) together (simultaneously) on Repurchase Interest (Y) in Ready Meal Products at PT Prima Freshmart in Serang City.